Edukasi Pencegahan Kekerasan Seksual di SMAN 1 Mulak Ulu Kabupaten Lahat Sumatera Selatan - Ayu Wijayanti; Linda Safitra (JURNAL ABDIMAS SERAWAI, 2023)
The rise of cases of sexual violence that occur in educational settings makes it important to do education to increase students' knowledge about forms of sexual violence and prevention efforts based on Law No. 12 of 2022 concerning Crimes of Sexual Violence. This activity was carried out using the approach of providing information and understanding to students and the school through the zoom platform, with the hope that students who are familiar with forms of sexual violence and laws regarding criminal acts of sexual violence can avoid sexual violence, both as victims and perpetrators. The achievement of this socialization goal can be seen from the students who can explain and classify forms of sexual violence according to Law No. 12 of 2022 and the school's commitment to creating a safe educational environment.